2017
DOI: 10.1021/acs.joc.7b01199
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Functionalized Carbazoles via a CAN-Catalyzed Multicomponent Process Comprising a C–H Activation Step

Abstract: The microwave-promoted three-component reaction between o-nitrochalcones, primary amines and β-dicarbonyl compounds in the presence of Ce(IV) ammonium nitrate constitutes the first example of a multicomponent carbazole synthesis. This reaction furnishes highly substituted and functionalized carbazole derivatives via a double annulation process that generates two C-C and two C-N bonds, with water as the only side product. Mechanistically, this transformation has some unusual features that include an intramolecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Although this method has the advantages of mild reaction conditions and low production cost, the yield of HQ is still low. In addition, the typical reductants or hydrogenation catalysts used in the reduction of BQ are based on Ni, Pd, Pt and other noble metal catalysts, which have many disadvantages such as higher cost of catalyst and harsh reaction conditions (high temperature and high pressure) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this method has the advantages of mild reaction conditions and low production cost, the yield of HQ is still low. In addition, the typical reductants or hydrogenation catalysts used in the reduction of BQ are based on Ni, Pd, Pt and other noble metal catalysts, which have many disadvantages such as higher cost of catalyst and harsh reaction conditions (high temperature and high pressure) …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the typical reductants or hydrogenation catalysts used in the reduction of BQ are based on Ni, Pd, Pt and other noble metal catalysts, which have many disadvantages such as higher cost of catalyst and harsh reaction conditions (high temperature and high pressure). [9][10][11][12] Enzymes can make the chemical reactions in organisms more efficient and accurate under extremely mild conditions. Hydrogenase, found in a variety of microorganisms, can efficiently catalyze the reduction of protons to hydrogen, and can be classified into [Fe]hydrogenase, [NiFe]-hydrogenase and [FeFe]-hydrogenase.…”
Section: Introductionmentioning
confidence: 99%
“…Th matic A-ring retains the ortho substitution pattern in a similar way to compounds 1 1b. The torsion angles between the atoms C8-C9-C1-C6 and C8-C7-C1′-C 177.6( 2 On the other hand, the dihedral angle formed between the main planes from t omatic rings is 11.38(18)°, which is comparatively smaller than those found in 1a a In the molecule, the nitro substituent attached to C4 is coplanar with the aromatic sy On the other hand, the dihedral angle formed between the main planes from the aromatic rings is 11.38 (18) • , which is comparatively smaller than those found in 1a and 1b. In the molecule, the nitro substituent attached to C4 is coplanar with the aromatic system, with a small torsion angle O4-N2-C4-C5 of 3.5(3) • , while the nitro group attached to C2 rotates out of the aromatic plane with a torsion angle of 69.1(2) • in order to minimize electrostatic repulsions with the C7=O7B carbonyl functional group.…”
Section: Structural Descriptionmentioning
confidence: 92%
“…We found that the chalcone with the nitro group at the ortho position develops the strongest anti-inflammatory protective effect, whereas the chalcone with the nitro group at the para position, showed the smallest effect [14]. Another important aspect of Crystals 2021, 11, 1589 2 of 12 some nitro chalcones is that they can be used as intermediates for synthesizing various heterocyclic compounds like indoles, thioaurones, carbazoles, sultams, benzothiophenes, quinolines and indolin-3-ones [15][16][17][18][19][20][21][22][23]. On the other hand, the nitro chalcones also find application as chemosensors for anion sensing [24].…”
Section: Introductionmentioning
confidence: 94%
“…In this context, we have described in preliminary fashion a diastereoselective three-component reaction that affords 1,3-diaryl-1,2,3,4-tetrahydrobenzene derivatives from alkylamines, β-ketoesters, and chalcones in the presence of catalytic Ce­(IV) ammonium nitrate (CAN) . Subsequently, we employed this reaction as the basis for one-pot routes to heterocyclic systems, such as quinazolines and carbazoles, without isolation of the intermediate terphenyls. Almost simultaneously with our initial communication, Shi reported another multicomponent process from malononitrile, nitrostyrenes, and arylmethylenemalononitriles leading to tetrahydro- m -terphenyls as diastereomer mixtures .…”
Section: Introductionmentioning
confidence: 99%